Active-Integrated Self-Oscillating Image Reject Mixer (IRM) - Yeap, Kim Huat (2018)
A conventional image reject mixer (IRM) is composed of an antenna, a radio frequency (RF) hybrid coupler, low noise amplifiers (LNAs), an external local oscillator (LO), mixers, intermediate frequency (IF) filters, and an IF hybrid coupler. The usage of the RF hybrid coupler and the external LO in the conventional IRM not only consume large space, the interconnections for the LO to the mixer as well as the interconnections for the RF hybrid coupler with the antenna and the mixer also result in losses. These drawbacks eventually affect the performance of the overall system. In view of these concerns, this research introduces a new architecture that eliminates the need of the RF hybrid coupler and external LO, entitled ‘Active-Integrated Self- Oscillating Image Reject Mixer (AISOIRM)’. The objectives of this research are to embed an active integrated antenna (AIA), a self-oscillating mixer (SOM), an IRM together into a single platform, and subsequently to implement, to characterize, as well as to evaluate the design in ensuring its performance is compatible with that of the conventional IRM. As a proof-of-concept work, this research realizes the AISOIRM architecture that operates in the 2.4 GHz Industrial, Scientific, and Medical (ISM) band. Its RF is assigned at 2.4 GHz and its LO frequency is 2.5 GHz. With this, the down-converted IF is 100 MHz. Two different topologies are designed. One adopts an E-shaped active antenna which supports an in-phase RF power divider function, namely the E-Topology. The other uses an F-shaped active antenna which supports a quadrature-phase RF power divider function, namely the F-Topology. Each of these topologies is configured in two different ways. The first configuration embeds both the antenna and IRM directly. Thereby, the configuration with the Eshaped antenna is named as ‘E-AISOIRM’ while the configuration with the F-shaped antenna is called ‘F-AISOIRM’. The second configuration cascades the amplifiers between the antenna and the IRM to increase the RF and LO signal levels that are delivered into the mixer. Thereby, the configuration with the E-shaped antenna is named as ‘E-Amp-AISOIRM’ while the configuration with the F-shaped antenna is called ‘F-Amp-AISOIRM’. The AISOIRM architecture eliminates the need of the RF hybrid coupler and external LO mainly by resonating its AIA at both the RF and LO frequencies. Aside from functioning as a passive radiator, the antenna also functions as an RF power divider, which replaces the need of the RF hybrid coupler. Correspondingly, the SOM is formed by merging the LO port of the antenna with the LO path of the IRM and the core mixer. This way, the LO signal is received from the antenna and injected into the mixer. Hence, the external LO source is omitted. To initiate the AISOIRM research, relevant literatures are first reviewed. This is followed by the theoretical calculations and simulations of the designs. During the theoretical calculations, the phase cancellation mechanism of both the E-AISOIRM and F-AISOIRM are analyzed mathematically. After this, all the four AISOIRM designs along with the antennas and sub-circuit designs are simulated using Advanced Design System (ADS). Three levels of simulation are performed. The ideal block design simulation performs a preliminary analysis on the overall designs, the circuit design simulation verify the schematics of the designs, and the circuitlayout design simulation finalizes the designs by taking into account the simulated effects of the layouts and printed circuit boards (PCBs) on the circuit designs. The finalized designs are then implemented, whereby the prototypes are assembled and characterized. The results obtained from the evaluations are subsequently analyzed. It is noted that the measured image rejection ratio (IRR) obtained for all the designs are greater than 15 dB, when biased near to the mixer transistor pinch-off at 0.7 V and supplied with the LNA optimum bias at 2.5 V. According to its measured results, the IRRs for the E-AISOIRM and the E-Amp-AISOIRM are 20.84 dB and 22.28 dB, respectively. Meanwhile, the measured IRRs for the F-AISOIRM and the F-Amp- AISOIRM are 21.72 dB and 21.52 dB, respectively. Generally, comparing between both the topologies, the E-Topology is preferred due to its much stable RF phase distribution, which thereon yields a much robust system. This is because the 0o RF phase division from the E-shaped antenna is determined by the symmetric geometry of its antenna structure. In converse, the 90o RF phase division of the F-shaped antenna depends on the exactness of its geometrical dimensions and the positions of its feed points instead. Hence, the RF phase of the F-shaped antenna is much sensitive to distortion than the RF phase of the E-shaped antenna. In overall, the AISOIRM architecture is able to perform image rejection with less external injection and more on self-operation through internal mechanism that contributes to more compact design. Therefore its miniaturized size is well suitable for wireless RF applications.